POTENSI APLIKASI TIKTOK SEBAGAI MEDIA PEMBELAJARAN BERINTEGRASI PROFIL PELAJAR PANCASILA PADA MATA PELAJARAN BAHASA INDONESIA - Indra Rasyid Julianto (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2023)
Indonesian language learning is one of the lessons that is the root of understanding in learning all subjects. At present, the civilization of the world of education has collided with digital technology that is rapidly developing which certainly has an influence on the formation of human character. The Pancasila student profile is a challenge in realizing the character of students to become a figure who is not only focused on cognitive aspects, but makes students have an identity as Indonesian citizens who have high moral values. The use of the Tiktok application can maximize the integration of the Pancasila student profile in Indonesian language learning which is the implication brought from the teacher as the main skipper in channeling information in the classroom. Things that must also be considered by teachers are the way of learning and the relationship in the teaching process involved in the understanding of the Pancasila student profile. This research uses a descriptive method of analysis regarding the Tiktok application which is the subject of research while its relation to the object is its utilization in integrating the Pancasila student profile in Indonesian language learning.